Current evidence on risk factors for knee osteoarthritis in older adults: a systematic review and meta-analysis. Issue 4 (April 2015) - Silverwood, V.; Blagojevic-Bucknall, M.; Jinks, C.; Jordan, J.L.; Protheroe, J.; Jordan, K.P.
Summary: Osteoarthritis (OA) is a leading cause of pain and disability and leads to a reduced quality of life. The aim was to determine the current evidence on risk factors for onset of knee pain/OA in those aged 50 and over. A systematic review and meta-analysis was conducted of cohort studies for risk factors for the onset of knee pain. Two authors screened abstracts and papers and completed data extraction. Where possible, pooled odds ratios (OR) were calculated via random effects meta-analysis and population attributable fractions (PAFs) derived. 6554 papers were identified and after screening 46 studies were included. The main factors associated with onset of knee pain were being overweight (pooled OR 1.98, 95% confidence intervals (CI) 1.57–2.20), obesity (pooled OR 2.66 95% CI 2.15–3.28), female gender (pooled OR 1.68, 95% CI 1.37–2.07), previous knee injury (pooled OR 2.83, 95% CI 1.91–4.19). Hand OA (pooled OR 1.30, 95% CI 0.90–1.87) was found to be non-significant. Smoking was found not to be a statistically significant risk or protective factor (pooled OR 0.92, 95% CI 0.83–1.01). PAFs indicated that in patients with new onset of knee pain 5.1% of cases were due to previous knee injury and 24.6% related to being overweight or obese. Clinicians can use the identified risk factors to identify and manage patients at risk of developing or increasing knee pain. Obesity in particular needs to be a major target for prevention of development of knee pain. More research is needed into a number of potential risk factors.